algebra

I need a step by step explanation on how to add these two equations

2x+3y=1
5x+3y=16

Subtract the first equation from the second. (Subtract left and right sides separately). This gives you
3x = 15
Then divide both sides by 3.
x = 5
Pretty easy, huh?
After you have x, you can get y by using any of the original equations.
10 + 3y = 1
Subtract 10 from both sides.
3y = -9
Divide both sides by 3
y = -3

2x + 3y =1
5x + 3y = 16

Multiply the 2nd equation by -1, then add them together like this:

2x + 3y = 1
-5x - 3y =-16
_________________

-3x = -15

Divide by -3 to get x =5. Now, substitute 5 for x in one of the equations and solve for y.

  1. 👍
  2. 👎
  3. 👁

Respond to this Question

First Name

Your Response

Similar Questions

  1. Maths!

    Find the sum of all multiples of 5 between 100 and 300 inclusive. Ans: 8200 I do not know how to do this. Really do appreciate step by step workings and explanation. Thanks!

  2. Geometry

    The sum of the angle measures of a polygon w/ "s" sides is 2880. Find "s" Please help with step-by-step explanation, so I can fully understand it. Thank you.

  3. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

  4. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

  1. Algebra

    Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A- step 4 B- step 1 C- step 2 D-

  2. CHEM

    The decomposition of nitrogen dioxide 2NO2-->2NO+O2 occurs in a two-step sequence at elevated tempatures. the first step lis NO2--> NO+O. predict a possible second step that, when combined with the first step, gives the complete

  3. Algebra

    Help PLZ. Which step could you use to start solving the system of equations below? x + y = 3 -3x - 2y = -7 Group of answer choices A. Multiply -3x - 2y = -7 by 2 and subtract it from x + y = 3 B. All of the above. C. Multiply x +

  4. physics help please!!!

    What is the angular momentum of a 2.5 kg uniform cylindrical grinding wheel of radius 19 cm when rotating at 1200 rpm? And how much torque is required to stop it in 5.7 s? Need help with step-by-step explanation.

  1. Quick math help

    In which step below does a mistake first appear in simplifying the expression? 0.5(-12c+6)-3(c+4)+10(c-5) Step 1: -6c+3-3(c+4)+10(c-5) Step 2: -6c+3-3c-12+10(c-5) Step 3: -6c+3-3c-12+10c-50 Step 4: 7c-41 Please help me!!! Thank

  2. Math

    April rewrote a quadratic function in vertex form. h(x)=5^2-30x+30 step 1 h(x)=5(x^2-6x+ )+30 step 2 h(x)=5(x^2-6x+9)+30-45 step 3 h(x)= 5(x-3)^2+15 In which step did they make a mistake? and how? Please help

  3. ALGEBRA HELP

    When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

  4. Help PLZ!!

    consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: -4 3 7 + 7 + (-3 4 7 ) Step 1: = -4 3 7 + (-3 4 7 ) + 7 Step 2: = -4 + (- 3 7 ) + (-3) + (- 4 7 ) + 7 Step 3: = -4 + (- 3 7 ) + (-

You can view more similar questions or ask a new question.